PERLINDUNGAN HUKUM BAGI PENGGUNA JASA ANGKUTAN UMUM BERDASARKAN UU NO.22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - NANCI YOSEPIN SIMBOLON (LP2MTBM MAKARIOZ, 2020)
Public transportation is a common facility that is often used as a means of transportation support as a tool to support economic development and development of society and industrial growth. For that public transportation service provider should pay attention to the security and comfort of their vehicles that used as a transport so that passengers as a service user can be fulfilled all his rights as should be without feeling harmed Because of public transport conditions that are less comfortable and less secure than the passengers themselves. But in fact there is still a neglected passenger rights in terms of comfort and safety of passengers as a public transportation service users so that the authors interested in the title of legal protection for users of public transport services under the LAW No. 22 year 2009 about traffic and public transport.The problems examined in this study are: (1) How is the legal arrangement for users of public transport services under law No. 22 of 2009? , (2) How is legal protection for users of public transport services under law No. 22 year 2009? , (3) What are the remedies that consumers can reach in the public transport service?This enelitian uses a normative juridical method of approach, which is the legal approach by reading, studying and describing the norms, provisions and opinions of legal experts. Based on normative juridical research, the data obtained comes from the library so that it is a literature research, which is research on secondary data which is then used as primarydata.